Rudolf Adamkovič Personal site


Converse

The

reversal

of the antecedent and the consequent of the conditional

\[\begin{equation*}
  P \implies Q
\end{equation*}
\]

in the form

\[\begin{align*}
  & P \impliedby Q \\
  \qor & Q \implies P,
\end{align*}
\]

which, unlike the contrapositive, is

not equivalent to the original statement,

so

\[\begin{equation*}
  (Q \implies P) \> \not \equiv \> (P \implies Q),
\end{equation*}
\]

but is

equivalent to its inverse,

so

\[\begin{equation*}
  (Q \implies P) \> \equiv \> (\lnot P \implies \lnot Q).
\end{equation*}
\]

(Levin, 2021, sec. 0.2)


© 2024 Rudolf Adamkovič under GNU General Public License version 3.
Made with Emacs and the secret alien technologies of yesteryear.